Enhancing the stabilities and electrochemical performances of LiNi0.5Co0.2Mn0.3O2 cathode material by simultaneous LiAlO2 coating and Al doping. (20th April 2021) - Sun, Yongjiang; Liu, Zhedong; Chen, Xiaochun; Yang, Xiaoping; Xiang, Fuwei; Lu, Wen
Abstract: Superior environmental and thermal stabilities and well-defined electrochemical performances of lithium nickel cobalt manganese oxide cathode materials are needed for next-generation high-performance and safe lithium-ion batteries, to which appropriate modification means have been proven to be crucial for enhancing the properties for these materials. Herein, we develop a facile in-situ approach to co-modify LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) cathode material with simultaneous lithium aluminum oxide (LiAlO2 ) coating and Al doping. Without any additional steps and reagents, the co-modification begins during the preparation of the hydroxide precursor of NCM523 and ends upon the calcination of the cathode material. Combining the synergistic effects from LiAlO2 coating and Al doping, the resultant Al-modified NCM523 possesses a robust protective layer as well as a well-ordered layered structure with enlarged lattice spacing, restrained cation mixing, and concentration-gradient-distributed Ni, thus exhibiting significantly enhanced environmental and thermal stabilities and electrochemical performances over its pristine counterpart. At a high active material content of 94.0 wt.% and a high mass loading of 19.5 mg cm −2 for the testing electrode, the optimized Al-modified NCM523 shows a high discharge capacity (168.4 mAh g −1 at 0.1 C), a high rate capability (capacity retains 67.8% at 3.0 C vs. 0.1 C), and a long cycle life (capacity retains 62.3% after charge / discharge at 0.5 C for 120 cycles). Reasonably, the unique in-situ co-modification approach developed in the present work can be applied for other NCMs with simultaneous LiAlO2 coating and Al doping. More broadly, apart from Al, this approach may be further extended to utilize other modification chemistries to co-modify NCMs and other cathode materials in situ for enhancing their stabilities and electrochemical performances.